The effectiveness of schema therapy on co-choice-avoidance and marital boredom in infertile women - Abbaszadeh, Azam; Khajevand Khoshli, Afsaneh; Asadi, Javanshir (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Infertility is one of the most important crises in life, which leads to psychological problems and stressful emotional experiences and affects the mutual relations of couples. This research was conducted with the aim of determining the effectiveness of schema therapy on co-choice-avoidance and marital boredom in infertile women. Methods: The research design was a quasi-experimental type of pre-test and post-test with a control group. The statistical population included all the infertile women of Sari who visited the infertility center in the first 6 months of 2019. 40 people were selected by available sampling method and were randomly divided into two groups of 20 people, experimental and control. Then, the people of the experimental group were trained in Young’s (1990) schema therapy protocol in 8 sessions of 90 minutes, and the control group did not receive any training. Bernstein et al.’s (1985) and Pines’ (1996) marital despondency questionnaires were used to collect information. The data were analyzed using multivariate analysis of covariance test. Results: The results showed that schema therapy is effective on partner choice-avoidance and marital boredom in infertile women in the post-test stage (P<0.05). Conclusion: According to the findings of this research, through schema therapy in a group way, it is possible to help to improve companionship-avoidance and marital boredom in infertile women.